Pengaruh Budaya Organisasi, Motivasi, Lingkungan Kerja Terhadap Kinerja Tenaga Pendidik (Madrasah Aliyah Negeri 1 Kota Malang) - Tara Ayudia Dianita; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis research is motivated by the rapidly growing business world, human resources can be used as well as possible in an educational institution. Educational institutions in combining the way of thinking of educators with the leadership of an institution in order to realize the goals of the organization including providing motivation for work, directing, guiding, coordinating the work of the leadership of subordinates. This study aims to determine organizational culture, motivation, work environment and to understand the influence of the work environment on the performance of educators in Senior High School 1 Malang City. This research takes quantitative research method where the source of the data used in this study is primary data where the data used is first verified and collected by researchers. In this study, primary data answers were obtained from 72 respondents who all consisted of educators in Senior High School 1 Malang City Environment. Keywords: Educational Institutions, Organizational Culture, Motivation